Szum na łączach. Kanadyjskie re-wizje: postkolonializm, TransKanada i Pierwsze Narody - Rzepa, Agnieszka (Er(r)go. Teoria - Literatura - Kultura, 2008)
Agnieszka Rzepa It’s a Bad Line. Canadian Re-visions: Postcolonialism, TransCanada and First Nations In the 1990s discussions on Canadian literature and culture were dominated by postcolonial discourses that coexisted with reflections on the Canadian model of multiculturalism. At the beginning of the 21st century the discussion on Canadian postcolonialism, and in particular on the position of Canadian literature in relation to postcolonial discourses, veered towards transcultural aspects of Canadian culture and literature. Such re-visions of the concept of postcolonial Canada as a “Second World” country have resulted in the emergence of an inspiring new concept of TransCanada, which – in the intention of its makers – should go beyond the postcolonial discourse, but which in fact remains entangled in it. The vision of TransCanada, just like the vision of postcolonial Canada, is complicated and problematized by the presence of the First Nations, their literatures and cultures. First Nations writers take active part in the developing discussion, inevitably focusing on the colonial dependence of the First Nations within Canada. Even though all the participants in the discussion have stressed the need to work out points of intersection and connection among different discourses on Canada, and in particular to take into account First Nations points of view, the net impression is often that of a “bad line call.” One of the most interesting aspects of this fluuctuating context is the potential positioning of First Nations literatures vis-a-vis Trans.Can.Lit.